Validity of The Use of Canva Video Media In Integrated Thematic Learning Based On Problem Based Learning Models in Elementary Schools - Chintya Nefillia; Reinita Reinita (Universitas Sebelas Maret, 2022)
This research began when researchers made observations in the field, that teachers had not developed integrated thematic learning media by utilizing existing technology. The sophistication of technology is found in the Canva application software and is supported by adequate facilities and infrastructure from schools that can be used as learning media. The purpose of this study is to develop Canva Video media on integrated thematic learning based on the Problem Based Learning (PBL) model in grade IV of a valid elementary school. The type of research carried out is Research and Development (R&D) with a 4D development model, namely Define, Design, Develop, and Disseminate. This research was conducted in elementary schools by collecting data techniques using questionnaires from material experts, linguists, and media experts. Canva is one of the online software used to create interesting learning videos. The results of the Canva Video Media development research developed obtained material validity test results of 91.6%, language validity test results of 87.5%, and media validity test results of 100%. Thus it can be concluded that canva Video Media on integrated thematic learning in grade IV elementary schools has been used validly.